Āryasampradāyapradearśaka Gāyatrībhāshya kā Hindī anuvāda - Miśra, Jagannātha (Gorakhā Granthapracāraka Maṇḍalī, 1911)
Interpretation of Gāyatrī, Vedic hymn, with exposition of method of meditating on its presiding deity Gāyatrī